2009
DOI: 10.1074/jbc.m802782200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Integrin αLβ2 Transmembrane Domain Interface by β2 Thr-686 Mutation Activates αLβ2 and Promotes Micro-clustering of the αL Subunits

Abstract: Integrins are type I heterodimeric cell adhesion molecules that mediate a wide array of biological processes. Integrin bidirectional signaling allows communication between the cell interior with its microenvironment. The integrin transmembrane domains (TMs) are the transducers of activation signal that is relayed from the cytoplasmic domains to the distal ligand binding site located in the ectodomain of the integrin and vice versa. In this study, we showed that the disruption of the ␣L␤2 TMs by mutation of a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Both Abs are able to activate CD18 integrins for ligand binding (32,33) and KIM127 has been shown to stabilize the unbent conformation of the integrin receptors (42). KIM127 binding is, furthermore, routinely used for investigating the level of integrin activation (41,(43)(44)(45). TS1/18 is a functionblocking Ab (31) that works through an allosteric mechanism (46) with an epitope either at or in close proximity to the Ca 2+ chelation site in the CD18 I-like domain (46,47) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both Abs are able to activate CD18 integrins for ligand binding (32,33) and KIM127 has been shown to stabilize the unbent conformation of the integrin receptors (42). KIM127 binding is, furthermore, routinely used for investigating the level of integrin activation (41,(43)(44)(45). TS1/18 is a functionblocking Ab (31) that works through an allosteric mechanism (46) with an epitope either at or in close proximity to the Ca 2+ chelation site in the CD18 I-like domain (46,47) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surface-biotinylated cells transfected with wild-type αLβ2 or OMC mutant were incubated with β2-specific mAb KIM127, which only recognizes β2 in a highly extended conformation that is a hallmark of integrin activation. 13,21,22 Cells were lysed, and mAb KIM127 was precipitated with protein A beads. Mutants αLS1071Fβ2 and αLG1075Fβ2 precipitated with mAb KIM127, whereas wild-type αLβ2 and αLβ2G694F only precipitated with mAb KIM127 in the presence of the activating agent Mg/ethylene glycol bis(baminoethyl ether) N,N′-tetraacetic acid (EGTA).…”
Section: Examining the Interface Of αLβ2 Tmsmentioning
confidence: 99%
“…β2 Thr686, which has been previously described to be important in the packing of αLβ2 TMs, is boxed. 13 The integrin αIIbβ3 TM-JM sequences are shown. The two C-terminal TM-cytoplasmic tail boundaries based on recent αIIbβ3 NMR studies of Lau et al 10 (blue broken line) and Yang et al 11 (red broken line) are shown.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were taken at 1-min intervals, but for clarity cell index is plotted as a function of time at 5-min intervals. D, the drawing illustrates the principle of FRET-based detection of integrin ␣L␤2 micro-clustering using the ␣L subunit having a C-terminal fusion of mCFP or mYFP as previously reported (9,43). E, shown are immunoblots of cell lysates of K562 transfected with integrin subunits ␣LmCFP, ␣LmYFP, ␤2, and HA-tagged kindlin-3 constructs.…”
Section: Methodsmentioning
confidence: 99%
“…We made use of a YFP-photobleach FRET-based assay (43) to determine whether kindlin-3 promotes integrin ␣L␤2 micro-clustering on K562 cells. ␣LmCFP and ␣LmYFP are fusion proteins of integrin ␣L subunit with C-terminal monomeric CFP and monomeric YFP, respectively (9).…”
Section: Kindlin-3 Is Required For Integrin ␣L␤2mentioning
confidence: 99%